Surface Localization of Zein Storage Proteins in Starch Granules from Maize Endosperm : Proteolytic Removal by Thermolysin and in Vitro Cross-Linking of Granule-Associated Polypeptides - Mu-Forster, Chen (American Society of Plant Physiologists, 1998)
Starch granules from maize (Zea mays) contain a characteristic group of polypeptides that are tightly associated with the starch matrix (C. Mu-Forster, R. Huang, J.R. Powers, R.W. Harriman, M. Knight, G.W. Singletary, P.L. Keeling, B.P. Wasserman [1996] Plant Physiol 111: 821–829). Zeins comprise about 50% of the granule-associated proteins, and in this study their spatial distribution within the starch granule was determined. Proteolysis of starch granules at subgelatinization temperatures using the thermophilic protease thermolysin led to selective removal of the zeins, whereas granule-associated proteins of 32 kD or above, including the waxy protein, starch synthase I, and starch-branching enzyme IIb, remained refractory to proteolysis. Granule-associated proteins from maize are therefore composed of two distinct classes, the surface-localized zeins of 10 to 27 kD and the granule-intrinsic proteins of 32 kD or higher. The origin of surface-localized δ-zein was probed by comparing δ-zein levels of starch granules obtained from homogenized whole endosperm with granules isolated from amyloplasts. Starch granules from amyloplasts contained markedly lower levels of δ-zein relative to granules prepared from whole endosperm, thus indicating that δ-zein adheres to granule surfaces after disruption of the amyloplast envelope. Cross-linking experiments show that the zeins are deposited on the granule surface as aggregates. In contrast, the granule-intrinsic proteins are prone to covalent modification, but do not form intermolecular cross-links. We conclude that individual granule intrinsic proteins exist as monomers and are not deposited in the form of multimeric clusters within the starch matrix.